An assessment of the nexus between youth livelihoods and urban poverty in slum communities: the case of Aboabo and Ayigya Zongo in Kumasi. - Essel, Victor (KNUST, 2025)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of MASTER OF PHILOSOPHY (MPHIL) PLANNING